GAMBARAN AKTIVITAS FISIK MAHASISWA SELAMA PEMBELAJARAN JARAK JAUH DAN MASA PANDEMIK COVID-19 : AKTIVITAS FISIK MAHASISWA SELAMA PEMBELAJARAN JARAK JAUH - Hendsun Hendsun; Yohanes Firmansyah; Andi Eka Putra; Hendry Agustian; Heiddy Chandra Sumampouw (Yayasan Pendidikan Medika Indonesia, 2021)
The Covid-19 pandemic has encouraged people to carry out all forms of activities at home, both work and study. This has an impact on reduced physical activity, especially among students. If this continues, it will increase the risk of developing non-communicable diseases. The purpose of this study was to provide an overview of students' physical activity during the Covid 19 pandemic or Studying from home. This research is a cross-sectional study using google form media (online survey) which took place from April 2020 to July 2020. The samples of this study were active students in semesters 1 to 14 who were studying online. The exclusion criteria for this study were incomplete data, duplication, and unavailability. The research variable is the calculation of Metabolic Equivalent for Task (MET) for each student's physical activity for 1 week, then classifies it into several activity categories. The results of this study obtained 197 respondents who met the inclusion criteria with a mean MET of 432.19 (178.64). Based on the classification of student activity, it was found that 168 (85.3%) were classified as light physical activity and 29 (14.7%) were classified as moderate physical activity, and none were classified as heavy physical activity. The conclusion of this study is that there are still many students whose physical activity is classified as sedentary. This should be of particular concern to prevent the incidence of non-communicable diseases in the future.